2006
DOI: 10.1136/aim.24.suppl.58
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Acupuncture for Chronic Pain Relief – Polymodal Receptors Are the Key Candidates

Abstract: Therapeutic benefits of acupuncture for chronic pain patients have been clearly identified in recent clinical trials. Underlying mechanisms of acupuncture action mediated by endogenous opioids have been well demonstrated. The existence of pain inhibitory systems in the central nervous system has also been clarified and acupuncture seems to be a potent stimulus for activating the analgesic systems, although the pain mechanisms in acute and chronic states are essentially different. On the other hand, the exact n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Recently, it has been suggested that Ctactile afferents may play a role in needle stimulation, 16 adding to the growing list of structures implicated, including polymodal receptors, 17 pressure receptors, muscle spindles and tendon organs 18 to name but a few. Langevin et al 19 20 have demonstrated that bi-directional rotation of a needle when placed deep in muscle tissue causes connective tissue fibres to get caught around the tip of the needle, stimulating intra-muscular primary afferents.…”
Section: Physiological Intention Of Needlingmentioning
confidence: 99%
“…Recently, it has been suggested that Ctactile afferents may play a role in needle stimulation, 16 adding to the growing list of structures implicated, including polymodal receptors, 17 pressure receptors, muscle spindles and tendon organs 18 to name but a few. Langevin et al 19 20 have demonstrated that bi-directional rotation of a needle when placed deep in muscle tissue causes connective tissue fibres to get caught around the tip of the needle, stimulating intra-muscular primary afferents.…”
Section: Physiological Intention Of Needlingmentioning
confidence: 99%
“…Acupuncture is a high-intensity stimulus that activates polymodal receptors and high-threshold, small-diameter Aβ, Aδ and C-fibers leading to inhibition of second-order nociceptive transmission cells by segmental and extrasegmental mechanisms [1,114,117]. Acupuncture activates structures on the descending pain inhibitory pathways, including the ventromedial medulla and periaqueductal gray (PAG) which have collaterals that project to many levels of the spinal cord [118 -120].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…These receptors are also assumed as the inputs for the development of diffuse noxious inhibitory controls. 29 So it is plausible that similar endogenous analgesic mechanisms might be activated by acupuncture and moxibustion.…”
Section: Mechanisms Of Analgesic Action Of Acupuncture and Moxibustionmentioning
confidence: 99%